Fractional Modeling of Driver’s Dynamics. Part2: Set Membership Approach for Steering Feel and Visual Feedback - Khemane, Firas; Malti†, Rachid; Moreau; Xavier (Journal of Applied Nonlinear Dynamics, 2026)
This paper is the second part of a study related to modeling drivers dynamics in the overall driving loop in the context of disturbance rejection and trajectory tracking. After a brief description of the experimental set-up, a fractional model for steering feel and visual feedback cases are proposed, and their parameters estimated. As expected in human reaction, data recorded from different experiments present a considerable dispersion, due to varying human reactions from one experiment to another. Such time-variant systems can be modeled using set membership methods which allow identifying a set of feasible models for healthy persons.